2010
DOI: 10.1158/0008-5472.can-09-1574
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Antitumor Mechanisms Downstream of Prophylactic Regulatory T-Cell Depletion

Abstract: Several reports have shown that prophylactic depletion of regulatory T cells (Treg) using various monoclonal antibodies (mAb) in mice can stimulate potent antitumor immune responses and prevent tumor development. These same depletion methods do not significantly suppress tumor growth in a therapeutic setting. Although different strategies to deplete FoxP3 + Treg have been used, no study has systematically compared these qualitatively for the effector mechanisms they each liberate. Herein, using prophylactic de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
63
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(72 citation statements)
references
References 33 publications
8
63
0
1
Order By: Relevance
“…Selective depletion of Foxp3 + Tregs leads to the regression of established tumors Several studies have shown that removal of CD25 + Tregs using depleting antibodies before the inoculation of tumor cells leads to their efficient rejection (13)(14)(15)(16)(17)(18)28); however, no tumor regression was observed in the majority of studies where CD25 + Tregs were depleted after inoculation of tumor cells (13,19,20). This therapeutic failure is most likely due to a concomitant elimination of tumor-specific, CD25-expressing effector T cells (13,19) or to the persistence of CD25 − Tregs (12), which cannot be targeted by anti-CD25…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Selective depletion of Foxp3 + Tregs leads to the regression of established tumors Several studies have shown that removal of CD25 + Tregs using depleting antibodies before the inoculation of tumor cells leads to their efficient rejection (13)(14)(15)(16)(17)(18)28); however, no tumor regression was observed in the majority of studies where CD25 + Tregs were depleted after inoculation of tumor cells (13,19,20). This therapeutic failure is most likely due to a concomitant elimination of tumor-specific, CD25-expressing effector T cells (13,19) or to the persistence of CD25 − Tregs (12), which cannot be targeted by anti-CD25…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, the main obstacle tempering successful immunotherapies and active vaccination might be the migration of Treg into tumors and their suppression of effective antitumor immune responses in the tumor microenvironment (2,9,11,12). Various groups have already investigated whether Treg removal using the depleting anti-CD25 antibody PC61 in mice might improve antitumor immunity, and it was shown that depletion of Tregs before the inoculation of tumor cells led to their efficient rejection (13)(14)(15)(16)(17)(18). In contrast, Treg depletion simultaneously with or after tumor inoculation resulted in no tumor regression (13,19,20), likely because the administered depleting antibodies also removed CD25-expressing effector T cells and CD25 − Foxp3 + Tregs persisted.…”
Section: Introductionmentioning
confidence: 99%
“…Inactivation Tregs in vivo was performed as previously reported 42,43 . Briefly, anti-CD25 (500 mg per mouse, eBioscience, #16-0251), anti-FR4 (25 mg per mouse; Biolegend, #125102) or a rat IgG1 isotype control Ab (eBioscience, #16-4301; Biolegend, #400622) were injected once at day À 1 before AdCre inhalation.…”
Section: Discussionmentioning
confidence: 99%
“…Through a variety of effector mechanisms, Tregs control inflammation and immunity in multiple contexts, including the regulation of Th1-, Th2-, and Th17-type inflammatory responses (8)(9)(10)(11). In preclinical models of both prophylactic and therapeutic cancer therapy, Tregs limit the generation of Th1 responses that drive CD8 + T cells and IFN-γ-dependent antitumor immunity (12)(13)(14)(15)(16). Furthermore, the mechanism of action of the humanized anti-CTLA-4 monoclonal antibody ipilimumab (Bristol Myers Squibb), which was given US FDA approval in 2011 (17) for treatment of advanced melanoma, depends on its ability to block Tregs and release APCs from Treg inhibition.…”
Section: Introductionmentioning
confidence: 99%